Compactness of the green operator of nonlinear diffusion equations: aplication to Boussinesq type systems in fluid dynamics - Diaz, J. I.; Vrabie, Ioan I. (Topological Methods in Nonlinear Analysis, 1994)
NO ABSTRACT